Adopting Technology Acceptance Model (TAM) and Theory of Planned Behavior (TPB) on Intention to Use EV Charging Station at Pertamina Green Energy Station - Dani Sanjaya Putra; Ahmad Muklason (Publikasi Indonesia, 2026)
The acceleration of the national energy transition has encouraged Pertamina to develop Green Energy Stations (GES) as integrated energy service centers, including the provision of Electric Vehicle (EV) Charging Stations. Although the electric vehicle ecosystem shows progressive growth, the utilization rate of public SPKLU is still not optimal, so an empirical study is needed on the determinants of intention to use. This study integrates the Theory of Planned Behavior (TPB) and Technology Acceptance Model (TAM) frameworks to analyze the influence of Attitude, Subjective Norm, Perceived Behavioral Control, Economic Factor, Green Advertising, Perceived Usefulness, and Perceived Ease of Use on the intention to use EV Charging Stations in Pertamina GES. The research approach used is quantitative with explanatory research. Primary data was collected through the distribution of an online questionnaire to 230 relevant respondents and analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS) through SmartPLS. The analysis includes validity, reliability, outer model, inner model, and hypothesis testing. The findings of the study showed that the variables Perceived Ease of Use, Subjective Norm, Green Advertising, and Economic Factor had a positive and significant effect on the intention to use EV Charging Station, while Perceived Usefulness, Attitude, and Perceived Behavioral Control were not significant and Attitude did not mediate the influence of other variables. These results confirm that the intention of use is more influenced by practical factors, social influences, environmental messages, and cost considerations. These findings form the basis for strategic recommendations to strengthen ease of service,